Whole-Genome Sequence of Multidrug-Resistant Methicillin-Resistant Staphylococcus epidermidis Carrying Biofilm-Associated Genes and a Unique Composite of SCCmec - Hisham N. Altayb; Hana S. Elbadawi; Othman Baothman; Imran Kazmi; Faisal A. Alzahrani; Muhammad Shahid Nadeem; Salman Hosawi; Kamel Chaieb (MDPI AG, 2022)
Staphylococcus epidermidis is part of the normal human flora that has recently become an important opportunistic pathogen causing nosocomial infections and tends to be multidrug-resistant. In this investigation, we aimed to study the genomic characteristics of methicillin-resistant S. epidermidis isolated from clinical specimens. Three isolates were identified using biochemical tests and evaluated for drug susceptibility. Genomic DNA sequences were obtained using Illumina, and were processed for analysis using various bioinformatics tools. The isolates showed multidrug resistance to most of the antibiotics tested in this study, and were identified with three types (III(3A), IV(2B&5), and VI(4B)) of the mobile genetic element SCCmec that carries the methicillin resistance gene (mecA) and its regulators (mecI and mecR1). A total of 11 antimicrobial resistance genes (ARGs) was identified as chromosomally mediated or in plasmids; these genes encode for proteins causing decreased susceptibility to methicillin (mecA), penicillin (blaZ), fusidic acid (fusB), fosfomycin (fosB), tetracycline (tet(K)), aminoglycosides (aadD, aac(6')-aph(2'')), fluoroquinolone (MFS antibiotic efflux pump), trimethoprim (dfrG), macrolide (msr(A)), and chlorhexidine (qacA)). Additionally, the 9SE strain belongs to the globally disseminated ST2, and harbors biofilm-formation genes (icaA, icaB, icaC, icaD, and IS256) with phenotypic biofilm production capability. It also harbors the fusidic acid resistance gene (fusB), which could increase the risk of device-associated healthcare infections, and 9SE has been identified as having a unique extra SCC gene (ccrB4); this new composite element of the ccr type needs more focus to better understand its role in the drug resistance mechanism.